Report of the Working Group on Agricultural Credit, Cooperation and Crop Insurance for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
Agriculture is of paramount importance to the economy of our country, not only because it gives direct employment to 2/3rd of our population but also because it is a provider of food, clothing, fodder and other basic necessities of life for the entire population. It also provides vital raw-material for our industry. Agriculture, therefore, is and will continue to be central to all strategies for planned social economic development of the country. Rapid growth of agriculture is essential not only to achieve self-reliance at national level but also for household food security and to tackle the problems of poverty, unemployment and environmental degradation.
Government of India Planning Commission
Government of India Planning Commission